Preservation of food from bacterial action - Zimmerman, L. Maud (My University, 1902)
Introduction: Man labors primarily to secure food, some of which may be destroyed by bacteria. Other men seek to discover preventives of bacterial decomposition so that it may be possible to preserve foods indefinitely. Hermetically sealing is the only positive means of preventing the growth of bacteria in foods. Bacteria are so abundant in water and air that it is impossible to keep them out of any exposed mass of food. Foods as well as animals have a natural resistance to bacterial action. For instance the skin of fruit prevents the attack of bacteria for a while. Of all methods employed for preserving fruit, for any length of time, none has so great a future before it as desiccation.
Citation: Zimmerman, L. Maud. Preservation of food from bacterial action. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Food Preservation; Bacteria; Theses; Manuscripts (documents)